An organic compound containing a nitrogen heterocyclic structure and a stacked OLED light-emitting device
By using nitrogen-containing heterocyclic compounds as n-type materials for CGL layer in OLED light emitting devices, the shortcomings of existing OLED devices in terms of driving voltage, luminous efficiency and lifetime are solved, and more efficient and more stable electroluminescent performance is achieved.
Patent Information
- Application Number
- CN202411960599.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-04
AI Technical Summary
The existing OLED light emitting devices have shortcomings in terms of driving voltage and luminous efficiency, and the material's heat resistance and film stability are poor, resulting in a short device life.
A nitrogen-containing heterocyclic compound is used as an n-type material of the CGL layer, and a stable N-metal coordination bond is formed through a bridge of a specific structure, thereby improving charge generation efficiency and device stability.
It effectively reduces the driving voltage of OLED devices, improves luminous efficiency and working life, and enhances the heat resistance and film stability of the material.
Smart Images

Figure CN119751485A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of organic photoelectric materials, and more specifically relates to an organic compound containing a nitrogen heterocyclic structure and a laminated OLED light-emitting device prepared by using the organic compound as N-CGL. Background Art
[0002] Organic light emitting diode (OLED) device technology can be used to manufacture new display products and new lighting products. It is expected to replace existing liquid crystal displays and fluorescent lighting, and has a wide range of applications. OLED light-emitting devices are like sandwich structures, including electrode material films and organic functional materials sandwiched between different electrode film layers. Various functional materials are superimposed on each other according to their uses to form OLED light-emitting devices. As a current device, when voltage is applied to the electrodes at both ends of the OLED light-emitting device and the electric field acts on the positive and negative charges in the organic layer functional material film layer, the positive and negative charges are further compounded in the light-emitting layer, generating OLED electroluminescence.
[0003] OLED optoelectronic functional materials used in OLED devices can be divided into two categories based on their uses, namely charge injection transport materials and luminescent materials. Furthermore, charge injection transport materials can be divided into electron injection transport materials, electron blocking materials, hole injection transport materials and hole blocking materials. As charge transport materials, they are required to have good carrier mobility, high glass transition temperature, etc. For OLED devices, electrons are injected from the cathode and then transferred to the main material through the electron transport layer, where they recombine with holes to generate excitons. Therefore, improving the injection and transport capabilities of the electron transport layer is conducive to reducing the device driving voltage while obtaining efficient electron-hole recombination efficiency.
[0004] In addition, in the stacked OLED, the stacked OLED is a series connection of two or more independent light-emitting units through a charge generation layer (CGL). Under the action of an external electric field, the electrons and holes generated by the CGL are respectively injected into adjacent light-emitting units, and are compounded into excitons in the light-emitting units to emit light. Therefore, the material selection and design of the CGL are key factors affecting the optoelectronic performance and life of the stacked layer. The CGL layer is constructed in the form of a pn structure, in which the p-type material mainly generates holes, while the n-type material generates electrons. Therefore, the performance of the n-type material in the CGL has a very large impact on the device performance. It is required to have efficient electron injection ability, transmission ability and high electronic durability. At the same time, the heat resistance and film stability of the material are also important. Materials with low heat resistance are not only prone to decomposition during material evaporation, but also thermal decomposition caused by the heat generated by the device when the device is working, and the material is degraded. In the case of poor phase stability of the material film, the material also undergoes thin film crystallization in a short time, resulting in direct layer separation of the organic film layer and device degradation. Therefore, the material used is required to have high heat resistance and good film stability.
[0005] Therefore, a material with excellent electron injection and transmission capabilities is developed, and the electron tolerance and stability are significantly enhanced. When applied to organic electroluminescent devices, it can effectively reduce the operating voltage of the device and improve the luminous efficiency and working life of the device.
[0006] In view of this, the present invention is proposed. Summary of the invention
[0007] In view of the above problems existing in the prior art, the present invention provides a nitrogen-containing heterocyclic compound, which bridges the nitrogen-containing compounds through a specific structure so that the compound has excellent electron injection and transmission capabilities, and the electron tolerance and stability are significantly enhanced. When applied to organic electroluminescent devices, it can effectively reduce the operating voltage of the device and improve the luminous efficiency and service life of the device.
[0008] The present invention provides a nitrogen-containing heterocyclic compound, the structure of which is shown in general formula (1):
[0009]
[0010] Where:
[0011] X1-X4 are the same as or different from each other and are selected from N, CR, and at least one of them is a N atom and the others are CR; preferably X1 is a N atom;
[0012] X5-X8 are the same as or different from each other and are selected from N, CR, and at least one of them is a N atom and the others are CR; preferably X5 is a N atom;
[0013] Most preferably, X1 and X5 are N atoms, and the rest are CR;
[0014] R is selected from H, D, T, C1-C10 alkyl, substituted or unsubstituted C6-C24 aryl, substituted or unsubstituted C6-C24 heteroaryl, wherein the heteroatom is selected from O, N, S;
[0015] L is selected from substituted or unsubstituted C6-C24 aryl, substituted or unsubstituted C6-C24 heteroaryl, wherein the heteroatom is selected from O, N, S;
[0016] Ar is selected from hydrogen, deuterium substituted or unsubstituted C6-C24 aryl, substituted or unsubstituted C6-C24 heteroaryl, wherein the heteroatom is selected from O, N, S;
[0017] R1 is a substituent on phenanthroline, each independently selected from H, D, T, C1-C10 alkyl, substituted or unsubstituted C6-C24 aryl, substituted or unsubstituted C6-C24 heteroaryl, wherein the heteroatom is selected from O, N, S; the number of R1 can be 0-6.
[0018] Further L is selected from substituted or unsubstituted phenylene, biphenyl, terphenyl, naphthyl;
[0019] Further Ar is selected from hydrogen, deuterated phenyl, biphenyl, naphthyl, pyridyl.
[0020] Further, the number of R1 can be 0, 1, 2, 3, 4, 5, or 6.
[0021] The above-mentioned "substituted" is monosubstituted or polysubstituted, selected from D, T, C1-C10 alkyl, substituted or unsubstituted C6-C24 aryl, substituted or unsubstituted C6-C24 heteroaryl, wherein the heteroatom is selected from O, N, S;
[0022] In the above technical solution, it is further preferred that the organic electroluminescent compound is any one of the following structures, but not limited thereto:
[0023]
[0024]
[0025]
[0026]
[0027]
[0028]
[0029]
[0030]
[0031]
[0032]
[0033]
[0034]
[0035]
[0036]
[0037]
[0038] Preparation method
[0039] The present invention also provides a method for preparing a nitrogen-containing heterocyclic compound, the process and steps are as follows:
[0040]
[0041] Wherein Hal1 and Hal2 are independently halogen, specifically Cl, Br or I. The rest are as defined above.
[0042] Under nitrogen protection, raw material A (1.0 eq) and raw material B (1.0 eq) were put into a mixed solution of toluene, ethanol and water, followed by ventilating for 3 times, and potassium carbonate (2.0 eq) and tetrakis(triphenylphosphine)palladium (0.01 eq) were added under nitrogen protection, stirred evenly, heated to 90-100° C., and refluxed for 8-10 hours. After the reaction was completed, the temperature was slightly lowered, and diatomaceous earth was used for filtration to remove salt and catalyst. After the filtrate was cooled to room temperature, it was washed with water three times, the organic phase was retained, and the aqueous phase was extracted with ethyl acetate; after the organic phases were combined, they were dried with anhydrous magnesium sulfate, and the solvent was removed with a rotary evaporator to obtain intermediate 1.
[0043] Under nitrogen environment, intermediate 1 (1.0 eq) was dissolved in toluene, raw material C (1.0 eq) was dissolved in toluene, and then raw material C was slowly added to the intermediate 1 solution, tri(dibenzylideneacetone)dipalladium (0.01 eq), tri-tert-butylphosphine (0.05 eq) and sodium tert-butyl alcohol (2.0 eq) were added thereto, the temperature was raised to 100-120°C, and the reaction was carried out for 8-10 hours. After the reaction was completed, the temperature was slightly lowered, and diatomaceous earth was used for filtering to remove salt and catalyst. After the filtrate was cooled to room temperature, it was washed three times with water, the organic phase was retained, and then the aqueous phase was extracted with ethyl acetate; after the organic phases were combined, they were dried with anhydrous magnesium sulfate, and the solvent was removed with a rotary evaporator, and dissolved in petroleum ether / ethanol, recrystallized, filtered, and the filter cake was rinsed with petroleum ether for multiple times, and dried in a 60°C oven for 5-7 hours to obtain the compound shown in general formula 1.
[0044] Raw material C can be diazacarbazole (such as CAS: 75449-34-2, 108349-62-8, 2015230-31-4, 1412913-78-0, 244-78-0, 26422-85-5, 875831-41-7, 7266-32-2, 77200-36-3), triazacarbazole (such as CAS: 2015230-32-5, 2015230-33-6), tetrazacarbazole (such as CAS: 1357360-48-5) and the like.
[0045] Beneficial Effects
[0046] It can be seen from the above technical solution that compared with the prior art, the beneficial effects of the present invention are as follows:
[0047] The invention provides a nitrogen-containing heterocyclic compound, wherein the molecular structure of the compound adopts the structure of phenanthroline and polyazacarbazole, and the compound is used as an n-type material of a CGL layer, and can form a stable N-metal coordination bond with metals such as Li or Yb to form a stable and flat organic-metal doped film, thereby inhibiting the oxidation of the metal and being beneficial to improving the charge generation efficiency and device stability.
[0048] When the compound of the present invention is used as an organic electroluminescent functional layer material in an OLED device, the device driving voltage can be effectively reduced and the device life and efficiency can be improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0050] Figure 1 This is the hydrogen nuclear magnetic resonance spectrum of compound 3 in Synthesis Example 1 of the present invention. DETAILED DESCRIPTION
[0051] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0052] Synthesis Example 1-Synthesis of Compound 3
[0053]
[0054] Under nitrogen protection, raw material A (1.0 eq) and raw material B (1.0 eq) were put into a mixed solution of toluene, ethanol and water, and then ventilated 3 times. Potassium carbonate (2.0 eq) and tetrakis(triphenylphosphine)palladium (0.01 eq) were added under nitrogen protection, stirred evenly, heated to 90°C, and refluxed for 8 hours. After the reaction was completed, the temperature was slightly lowered, and diatomaceous earth was used for filtration to remove salt and catalyst. After the filtrate was cooled to room temperature, it was washed with water three times, the organic phase was retained, and the aqueous phase was extracted with ethyl acetate; after the organic phases were combined, they were dried with anhydrous magnesium sulfate, and the solvent was removed with a rotary evaporator to obtain intermediate 1. (Yield, 75.6%)
[0055] Under nitrogen environment, intermediate 1 (1.0 eq) was dissolved in toluene, raw material C (1.0 eq) was dissolved in toluene, and then raw material C was slowly added to the intermediate 1 solution, tri(dibenzylideneacetone)dipalladium (0.01 eq), tri-tert-butylphosphine (0.05 eq) and sodium tert-butyl alcohol (2.0 eq) were added thereto, and the temperature was raised to 120°C and reacted for 10 hours. After the reaction was completed, the temperature was slightly lowered, and diatomaceous earth was used for filtering to remove salt and catalyst. After the filtrate was cooled to room temperature, it was washed three times with water, and the organic phase was retained. Then, the aqueous phase was extracted with ethyl acetate; after the organic phases were combined, they were dried with anhydrous magnesium sulfate, and the solvent was removed with a rotary evaporator, and dissolved in petroleum ether / ethanol, recrystallized, filtered, and the filter cake was rinsed with petroleum ether for several times, and dried in a 60°C oven for 5 hours to obtain compound 3; (yield, 66.7%)
[0056] The obtained compound 3 was tested and analyzed, and the results were as follows:
[0057] HPLC purity: >99.95%.
[0058] Mass spectrometry test: theoretical value is 499.18; tested value is 500.19.
[0059] Elemental Analysis:
[0060] Calculated values: C, 81.74; H, 4.24; N, 14.02.
[0061] The test values are: C, 81.58; H, 4.58; N, 14.32.
[0062] Synthesis Example 2-Synthesis of Compound 12
[0063]
[0064] Under nitrogen protection, raw material A (1.0 eq) and raw material B (1.0 eq) were put into a mixed solution of toluene, ethanol and water, and then ventilated 3 times. Potassium carbonate (2.0 eq) and tetrakis(triphenylphosphine)palladium (0.01 eq) were added under nitrogen protection, stirred evenly, heated to 90°C, and refluxed for 8 hours. After the reaction was completed, the temperature was slightly lowered, and diatomaceous earth was used for filtration to remove salt and catalyst. After the filtrate was cooled to room temperature, it was washed with water three times, the organic phase was retained, and then the aqueous phase was extracted with ethyl acetate; after the organic phases were combined, they were dried with anhydrous magnesium sulfate, and the solvent was removed with a rotary evaporator to obtain intermediate 1. (Yield, 73.8%)
[0065] Under nitrogen environment, intermediate 1 (1.0 eq) was dissolved in toluene, raw material C (1.0 eq) was dissolved in toluene, and then raw material C was slowly added to the intermediate 1 solution, tri(dibenzylideneacetone)dipalladium (0.01 eq), tri-tert-butylphosphine (0.05 eq) and sodium tert-butyl alcohol (2.0 eq) were added thereto, and the temperature was raised to 120°C and reacted for 10 hours. After the reaction was completed, the temperature was slightly lowered, and diatomaceous earth was used for filtering to remove salt and catalyst. After the filtrate was cooled to room temperature, it was washed three times with water, and the organic phase was retained. Then, the aqueous phase was extracted with ethyl acetate; after the organic phases were combined, they were dried with anhydrous magnesium sulfate, and the solvent was removed with a rotary evaporator, and dissolved in petroleum ether / ethanol, recrystallized, filtered, and the filter cake was rinsed with petroleum ether for several times, and dried in a 60°C oven for 5 hours to obtain compound 12; (yield, 64.2%)
[0066] The obtained compound 12 was tested and analyzed, and the results were as follows:
[0067] HPLC purity: >99.95%.
[0068] Mass spectrometry test: theoretical value is 549.20; tested value is 550.21.
[0069] Elemental Analysis:
[0070] Calculated values: C, 83.04; H, 4.22; N, 12.74.
[0071] The test values are: C, 82.88; H, 4.63; N, 13.05.
[0072] Synthesis example 3-20
[0073] The synthesis methods of other compounds are the same as those in the above examples, which are not described one by one here. The mass spectrometry test is performed using a Waters XEVO TQD mass spectrometer, which has low precision, and is tested using an ESI source. The mass spectrometry test values, molecular formulas, and yields of other synthesis examples are shown in Table 1 below:
[0074]
[0075]
[0076] Device Example 1
[0077] The device embodiments of the present invention are as follows:
[0078] Anode: The transparent substrate layer is a transparent PI film, and the ITO anode layer is washed, that is, alkali washing, pure water washing, drying, and then ultraviolet-ozone washing to remove organic residues on the surface of the anode layer;
[0079] Hole injection layer: On the washed anode layer, HT-1 and P-1 with a thickness of 10 nm were deposited by vacuum deposition apparatus. The mass ratio of HT-1 to P-1 was 97:3 as a hole injection layer. The speed was 1 angstrom / second.
[0080] Hole transport layer: On the hole injection layer, HT-1 with a thickness of 20 nm was then evaporated at a rate of 1 angstrom / second as a hole transport layer.
[0081] Electron blocking layer: EB-1 with a thickness of 5 nm was then evaporated on the hole transport layer as an electron blocking layer at a rate of 0.5 angstroms / second.
[0082] Light-emitting layer: After the above-mentioned electron blocking material is evaporated, the light-emitting layer of the OLED light-emitting device is manufactured. Its structure includes the OLED light-emitting layer using BH-1 as the main material and BD-1 as the doping material. The doping ratio of the doping material is 3% by weight. The thickness of the light-emitting layer is 20nm and the speed is 1 angstrom / second.
[0083] Hole blocking layer: After the above-mentioned light-emitting layer, 5 nm of HB-1 was evaporated as a hole blocking layer; 0.5 Å / sec.
[0084] Electron transport layer: After the hole blocking layer, 10 nm of ETM-1:LiQ=5:5 was vacuum-deposited at a rate of 0.5 angstroms / second as an electron transport layer.
[0085] Charge generation layer (N-CGL layer): On the electron transport layer, an N-type charge generation layer (N-CGL layer) is evaporated by a vacuum evaporation device. Its structure is Yb: compound 3 (the doping ratio of Yb is 5% by weight), the film thickness is 20nm, and the speed is 0.5 angstroms / second.
[0086] P-CGL layer: On the N-CGL layer, a co-evaporation layer of HT-1 and P-1 with a film thickness of 10 nm was evaporated using a vacuum evaporation device. The mass ratio of HT-1 to P-1 was 95:5 as the P-CGL layer at a rate of 1 angstrom / second.
[0087] Hole transport layer 2: HT-1 was then evaporated to a thickness of 35 nm as the hole transport layer 2 at a rate of 1 angstrom / second.
[0088] Electron blocking layer 2: Subsequently, EB-1 was evaporated on the hole transport layer 2 to a thickness of 5 nm as the electron blocking layer 2 .
[0089] Light-emitting layer 2: After the above-mentioned electron blocking material is evaporated, the light-emitting layer 2 of the OLED light-emitting device is manufactured. Its structure includes that the OLED light-emitting layer 2 uses BH-1 as the main material and BD-1 as the doping material. The doping ratio of the doping material is 3% by weight. The thickness of the light-emitting layer is 20nm and the speed is 1 angstrom / second.
[0090] Hole blocking layer 2: After the above-mentioned light-emitting layer 2, continue to vacuum evaporate 5nm of HB-1. This layer is the hole blocking layer 2 at a rate of 0.5 angstroms / second.
[0091] Electron transport layer 2: On the hole blocking layer 2, 30 nm of ETM-1:LiQ=5:5 was evaporated as the electron transport layer 2 at a rate of 0.5 angstroms / second.
[0092] Electron injection layer: On the electron transport layer 2, metal Yb with a film thickness of 1 nm was formed by vacuum evaporation.
[0093] Cathode layer: A 15 nm Mg:Ag electrode layer was evaporated, and the mass ratio of Mg to Ag was 1:9. This layer was the cathode layer.
[0094] Light extraction layer: CPL-1 with a thickness of 65 nm was vacuum-deposited on the cathode at a deposition rate of 1 angstrom / second to serve as a light extraction layer.
[0095] Then the vapor-deposited substrate is packaged. First, the cleaned cover is coated with UV glue using glue coating equipment, and then the coated cover is moved to the pressing section, the vapor-deposited substrate is placed on the upper end of the cover, and finally the substrate and cover are bonded by bonding equipment, and the UV glue is cured by light.
[0096] The structural formula of the materials used is shown below:
[0097]
[0098] Device Example 2-Device Example 31 Referring to the above method, the compound 3 used in Device Example 1 is replaced by Compound 12, Compound 2, Compound 5, Compound 8, Compound 11, Compound 17, Compound 24, Compound 26, Compound 35, Compound 44, Compound 51, Compound 60, Compound 73, Compound 84, Compound 89, Compound 96, Compound 99, Compound 104, Compound 108, Compound 122, Compound 123, Compound 128, Compound 135, Compound 143, Compound 152, Compound 155, Compound 158, Compound 164, Compound 170, and Compound 179 as compounds in the CGL layer to prepare corresponding organic electroluminescent devices.
[0099] Device Comparison
[0100] Comparative Examples 1-4 provide an organic electroluminescent device. The only difference between the preparation method of the organic electroluminescent device and that of Example 1 is that the organic electroluminescent device uses existing comparative compounds a, b, c, and d to replace the CGL layer (Compound 3) in Example 1 to prepare Comparative Examples 1-4. The chemical structures of the comparative compounds a, b, c, and d are:
[0101]
[0102] Device data
[0103] The driving voltage, luminous efficiency and life of the organic electroluminescent devices obtained in the above device embodiments and device comparative examples 1-4 were characterized at a brightness of 1000 (nits). The test results are shown in Table 2 below:
[0104] Table 2 - Device data of the present invention
[0105]
[0106]
[0107] As can be seen from Table 2, in the stacked device, the compound of the present invention is used as a CGL material. Compared with the comparative material, the device voltage is reduced, and the device efficiency and device life are improved, which further shows that the compound of the present invention has good technical effects when used as a CGL material in the stacked OLED device. It should be noted that BI in Table 2 = luminous efficiency / CIEy, which reflects that the luminous efficiency of the blue light OLED device is affected by the chromaticity. CIEy is not shown in the table because it is tested that CIEy hardly changes, fluctuates in a very small range of 0.040 to 0.042, and most of them are 0.041.
[0108] The polynitrogen carbazole of the present invention is a bipolar substance. The 9-position N atom of the polynitrogen carbazole has electron-donating ability, and the azabenzene structure has electron-withdrawing ability. Therefore, the HOMO energy level is relatively deep, and the LUMO energy level is close to the HOMO energy level of P-CGL. Therefore, interlayer electron hopping is achieved, more free mobile electrons are generated, and performance improvement is achieved.
[0109] It will be apparent to those skilled in the art that many modifications and variations of the present invention are possible without departing from the spirit and scope of the present invention. It is therefore contemplated that the present invention covers modifications and variations of the present invention provided within the scope of the appended claims and their equivalents.
[0110] The various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.
[0111] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A nitrogen-containing heterocyclic compound, the structure of which is shown in general formula (1): Where: X1-X4 are the same as or different from each other and are selected from N, CR, and at least one of them is a N atom and the others are CR; X5-X8 are the same as or different from each other and are selected from N, CR, and at least one of them is a N atom and the others are CR; R is selected from H, D, T, C1-C10 alkyl, substituted or unsubstituted C6-C24 aryl, substituted or unsubstituted C6-C24 heteroaryl, wherein the heteroatom is selected from O, N, S; L is selected from substituted or unsubstituted C6-C24 aryl, substituted or unsubstituted C6-C24 heteroaryl, wherein the heteroatom is selected from O, N, S; Ar is selected from hydrogen, deuterium substituted or unsubstituted C6-C24 aryl, substituted or unsubstituted C6-C24 heteroaryl, wherein the heteroatom is selected from O, N, S; R1 is a substituent on phenanthroline, each independently selected from H, D, T, C1-C10 alkyl, substituted or unsubstituted C6-C24 aryl, substituted or unsubstituted C6-C24 heteroaryl, wherein the heteroatom is selected from O, N, S; the number of R1 can be 0-6.
2. A compound according to claim 1, characterized in that: X1 is a N atom.
3. A compound according to claim 1, characterized in that: X5 is a N atom.
4. A compound according to claim 1, characterized in that: X1 and X5 are N atoms, and the rest are CR.
5. A compound according to claim 1, characterized in that: L is selected from substituted or unsubstituted phenylene, biphenyl, terphenyl, naphthyl; Ar is selected from hydrogen, deuterated phenyl, biphenyl, naphthyl, pyridyl.
6. A compound according to claim 1, characterized in that: The number of R1 can be 0, 1, 2, 3, 4, 5, or 6.
7. A compound according to claim 1, characterized in that: The compound is any one of the following structures:
8. A method for preparing the compound according to any one of claims 1 to 7, characterized in that: The process is as follows: wherein Hal1 and Hal2 are independently halogen; and the rest are as defined above.
9. The preparation method according to claim 8, characterized in that: Hal1 and Hal2 are independently Cl, Br or I.